HELP EFFECT OF CERUMINOLYTIC IN TOPIC THERAPY OF DOGS (Canis lupus familiaris) WITH EXTERNAL OTITIS CERUMINOUS - Mueller, Eduardo Negri (2013)
We evaluated the help effect of ceruminolytic in ceruminous external otitis in dog’s ears. Dogs with bilateral ceruminous external otitis, whose ears were evaluated by palpation, inspection, otoscopy and fungal and bacterial culture were studied. For the treatment, carried out twice a day during 15 days, the animals were divided into two groups, A and B. The animals in group A were treated with ceruminolytic and otological solution, containing, respectively, salicylic acid and aminoglycoside, while the animals in group B were treated only with otological solution. Clinical and microbiologic evaluations were performed on 0 and 15 days of treatment. Twenty dogs (n=40 ears), with at least erythema in the otoscopy and moderate to intense ceruminous exsudate. Besides these, we observed more erythema (n=16 in both groups) and exsudate in the acoustic conch (n=14 and n=11, respectively, groups A and B) and itch (n=13 and n=11, respectively, groups A and B).  On the 15th day, we observed reduction of all clinical signals, except stenosis, which did not change in any of the groups, and pain, which increased in group A. The microorganisms Malassezia pachydermatis e Staphylococcus sp. reduced in treatment B with statistical significance. Bacteria were more sensitive to gentamicin. The use of ceruminolytic associated to otological solution reduced the external ottis clinical signals, mainly exsudate and smell in the acoustic conch and the quantity of cerumen in the otoscopy, without interfering in the microorganisms reduction. KEYWORDS: exsudate; otological solution; salicylic acid.